Rabbit model of Lyme borreliosis: erythema migrans, infection-derived immunity, and identification of Borrelia burgdorferi proteins associated with virulence and protective immunity. - Foley, D M (1995)
Erythema migrans (EM), persistent skin infection, and visceral dissemination can be induced reproducibly in the adult male New Zealand White rabbit by intradermal injection of as few as 10(3) Borrelia burgdorferi. EM was found to persist for 7 +/- 3 d. Skin culture positivity (infection) cleared within a mean of 6.7 +/- 1.4 wk after infection and similarly visceral infection was not demonstrated after 8 wk; infection-derived immunity to intradermal challenge was evident 5 mo after initial infection. The extent of the protection against EM and dermal infection induced by untreated infection was directly related to the extent of prior in vitro passage of the B31 strain. Initial infection with as few as 4 x 10(3) B31 passage 4 induced complete protection against EM and skin infection upon subsequent challenge with 4 x 10(7) B31, passage 4. Initial infection with B31 passage 27 led to partial protection against EM along with complete protection against skin infection. Initial infection with passage 47 led to partial protection against EM, but conferred no protection against skin infection. Using serum from rabbits fully immune to reinfection, we defined a set of B. burgdorferi proteins present in virulent B31, but absent in the avirulent American Type Culture Collection B31 strain, termed "va" for virulent strain associated. The va proteins of B31 passages 1, 27, and 47 differed strikingly, thus raising the possibility that these changes may relate in a causal way to the differences in induction of protective immunity observed.